Influence of Palm Oil Mill Effluents on Selected Soil Physicochemical Properties and Soil Enzyme Activities - Uroko, Robert Ikechukwu; Aaron, Chinomso Friday; Uche, Mercylyn Ezinne; Aguwamba, Chinedu; Nweje-Anyalowu, Paul Chukwuemaka (Hasanuddin University, 2025)
Palm oil mill effluent (POME) is applied on cultivated farmlands at various stages by many farmers in southeastern Nigeria with many reporting that it helps to improve crop yield and productivity despite no availability of data to support their claims. This study was therefore designed to investigate the impact of POME on soil physicochemical parameters and soil enzyme activities in soil samples from POME irrigated farmlands. In this study, top and subsoil samples from control farmland unirrigated with POME, dumpsites and 10 m away from POME dumpsites in six different farmlands irrigated with POME labelled A – F were investigated using standard analytical procedures. The results of physicochemical properties of the soils including nitrogen, phosphorus, organic carbon, organic matter, cation exchange capacity and exchangeable cations indicated significant (P<0.05) in topsoil and sub-soils containing POME when compared with their corresponding control1 soils. The lipase activities of topsoil from dumpsites A-E and subsoil 10m away from dumpsite C indicated a significant increase (P<0.05) relative to the corresponding control soils. The effluents caused a significant (P<0.05) decrease in the dehydrogenase and catalase activities of top-soils and sub-soils from each of the dumpsites and 10m away from respective dumpsites when compared with their respective control soils. The findings of this study revealed that the application of POME on soil increases the contents of soil organic carbon, organic matter, exchangeable cations, and cation exchange capacity interfere with enzyme activities.